Magnetostratigraphy and stable isotope stratigraphy of the middle-Eocene succession of the Ainsa basin (Spain): New age constraints and implications for sediment delivery to the deep waters. (October 2021) - Läuchli, Charlotte; Garcés, Miguel; Beamud, Elisabet; Valero, Luis; Honegger, Louis; Adatte, Thierry; Spangenberg, Jorge E.; Clark, Julian; Puigdefàbregas, Cai; Fildani, Andrea; de Kaenel, Eric; Hunger, Teodoro; et al.
Abstract: Stratigraphic cycles preserved in sedimentary successions are controlled by the interaction of tectonics, climate, sediment supply and sea-level variations. Understanding the influence of these drivers on sedimentary systems dynamics is crucial to understand and extract information from sedimentary archives. In the deep marine deposits of the Ainsa foreland basin (lower to middle Eocene, southern central Pyrenees, Spain), the origin of well-preserved cyclicity between channelized sandy submarine fans and hemipelagic deposits remains subject to debate because of the absence of chronostratigraphic constraints on high resolution geochemical proxies. Here, we contrast a combination of newly acquired and legacy geochemical datasets (carbon and oxygen stable isotopes, organic matter content, major and trace elements and the mineralogical composition of bulk hemipelagic sediments) tuned by a new age model to global "target" curves to discuss the possible drivers of the stratigraphic cycles found in the deep marine sediment gravity flow deposits of the Hecho Group. Our new age model is based on magnetostratigraphic and biostratigraphic datasets acquired on a composite section going from the Banaston system to the distal deposits of the Sobrarbe deltaic complex. Four major polarity zones are identified in the studied succession covering the time span from C21n (lower members of the Banaston system) to C19r (Sobrarbe deltaic complex). Our age model is corroborated by the identification of the nannoplankton zone NP16 in the Guaso system (C20n). Comparison between global carbon isotope curve and local isotope dataset shows some differences, suggesting the preservation of a local isotope signal modulated by eustatism, changes in the environment of deposition and/or restriction in water circulation in the Ainsa basin. Yet, comparison of the stratigraphic record with global sea-level curves highlights that sands are mainly delivered to the basin during lowstands, pointing to the important role of eustasy even in an active foreland tectonic context. The exception to the rule is the Banaston member II, whose deposition during a sea-level highstand seems to be controlled by the growth of tectonic structures. Highlights: New age model for the deep marine sediment gravity flow deposits of the upper Hecho Group in the Ainsa basin. Complete stable carbon and oxygen isotope records for the Hecho group. Dominant but not exclusive delivery of sands during sea-level lowstands.